2019
DOI: 10.1145/3359163
|View full text |Cite
|
Sign up to set email alerts
|

Hateful People or Hateful Bots?

Abstract: Arabic Twitter space is crawling with bots that fuel political feuds, spread misinformation, and proliferate sectarian rhetoric. While efforts have long existed to analyze and detect English bots, Arabic bot detection and characterization remains largely understudied. In this work, we contribute new insights into the role of bots in spreading religious hatred on Arabic Twitter and introduce a novel regression model that can accurately identify Arabic language bots. Our assessment shows that existing tools that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…When analyzing the tweets in our dataset, we found a trend of Quran tweets being tagged with the hashtag "# <du'a>" which translates to "#prayer'. We suspected that this trend might indicate bot activity, given that it was very consistent and frequent, which is also noted by [7]. After further investigation of these tweets metadata, we found that these tweets were automatically generated through an app.…”
Section: Detection Of Automated Contentsupporting
confidence: 55%
See 3 more Smart Citations
“…When analyzing the tweets in our dataset, we found a trend of Quran tweets being tagged with the hashtag "# <du'a>" which translates to "#prayer'. We suspected that this trend might indicate bot activity, given that it was very consistent and frequent, which is also noted by [7]. After further investigation of these tweets metadata, we found that these tweets were automatically generated through an app.…”
Section: Detection Of Automated Contentsupporting
confidence: 55%
“…The second strand of literature centers the different ways religious communities utilize new media forms like social media as platforms for expressing, discussing, and practicing their religious identities [6,7,9,12,19,21,26,38,51]. We reference this work to better situate our study at the intersection of both lines of research on religion and technology.…”
Section: Religion and Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…As such, we were able to detect and classify the political bots operating in Spain's 2019 elections, as well as to develop the country's first political bot classifier. Consequently, we were able to overcome the problems that arise upon using classifiers designed for texts written in English (Albadi et al 2019).…”
Section: Discussionmentioning
confidence: 99%